STUDI PERBANDINGAN PEMBERIAN POC KULIT PISANG KEPOK DAN POC KULIT BUAH NANAS TERHADAP PERTUMBUHAN TANAMAN PAKCHOY: STUDI PERBANDINGAN PEMBERIAN POC KULIT PISANG KEPOK DAN POC KULIT BUAH NANAS TERHADAP PERTUMBUHAN TANAMAN PAKCHOY - Royan, Royan Pebriawan (Jurnal Teknologi Lingkungan, 2025)
Pakchoy mustard greens (Brassica rapa L) is one type of vegetable that comes from cina, this vegetable is quite popular with the people of Indonesia. Pakchoy plants require high nutrient availability to encourage plant metabolism so that they can produce maximum plant production. Pakchoy plant cultivation techniques currently only rely on conventional farming using inorganic fertilizers to increase production. One alternative to increase Pakchoy plant production and to reduce the use of inorganic fertilizers on a home production scale is to use liquid organic fertilizer, the basic ingredients for making liquid organic fertilizer are kepok banana peel and pineapple peel. The purpose of this study was to compare the growth results of pakchoy plants using Liquid Organic Fertilizer from kepok banana peel and pineapple peel. The research method used in this study was experimental with RAL design and 3 repetitions in the provision of liquid organic fertilizer from kapok banana and pineapple peels. Data collection techniques were in the form of literature studies, observation, and documentation. Data analysis techniques used one-way anova. The results of this study showed that there was a significant difference between the growth of pakchoy plants with the provision of POC from pineapple peel and kepok banana peel, where the provision of POC from pineapple peel provided the highest growth data for plant height parameters and number of leavesof pakchoy plants.